SU(2) Quantum Yang–Mills Thermodynamics: Some Theory and Some Applications - Ralf Hofmann (Universe, 2018)
In the first part of this talk, we review some prerequisites for and essential arguments involved in the construction of the thermal-ground-state estimate underlying the deconfining phase in the thermodynamics of SU(2) Quantum Yang⁻Mills theory and how this structure supports its distinct excitations. The second part applies deconfining SU(2) Yang⁻Mills thermodynamics to the Cosmic Microwave Background in view of (i) a modified temperature-redshift relation with an interesting link to correlation-length criticality in the 3D Ising model, (ii) the implied minimal changes in the dark sector of the cosmological model, and (iii) best-fit parameter values of this model when confronted with the spectra of the angular two-point functions temperature-temperature (TT), temperature-E-mode-polarisation (TE), E-mode-polarisation-E-mode-polarisation (EE), excluding the low-l physics. The latter, which so far is treated in an incomplete way due to the omission of radiative effects, is addressed in passing.